ENVIRONMENTAL PROTECTION'S IMPORTANCE IN GUARANTEEING FOOD SAFETY - Xudayberdiyeva Filyura Mirzamashrabovna (American Journals Publishing, 2025)
Environmental protection plays a crucial role in ensuring food safety by preserving the natural resources necessary for agriculture and promoting sustainable practices. As climate change, soil degradation, and water scarcity become more prevalent, safeguarding the environment is essential to ensure that future generations can access safe, nutritious food. Effective environmental protection strategies, such as reducing pollution, improving water management, and promoting biodiversity, can directly enhance agricultural productivity and reduce the risks associated with foodborne diseases. Integrating environmental policies with food safety regulations ensures a more resilient food system that can withstand environmental challenges and provide long-term food security.
Keywords: Environmental protection, food safety, sustainable agriculture, climate change, water management, biodiversity, foodborne diseases, food security.